Capital Structure and Product-Market Competition: Empirical Evidence from the Supermarket Industry - Chevalier, Judith A. (American Economic Review, 1995)
This paper establishes an empirical link between firm capital structure and product-market competition using data from local supermarket competition. First, an event-study analysis of supermarket leveraged buyouts (LBOs) suggests that a LBO announcement increases the market value of the LBO chain's local rivals. Second, the author shows that supermarket chains were more likely to enter and expand in a local market if a large share of the incumbent firms in the local market undertook LBOs. The study suggests that leverage increases in the late 1980s led to softer product-market competition in this industry. Copyright 1995 by American Economic Association.